2016
DOI: 10.1186/s12885-016-2509-5
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 expression is associated with a cancer stem cell state and down-regulation of CDX2 in colorectal cancer

Abstract: BackgroundTo improve current treatment strategies for patients with aggressive colorectal cancer (CRC), the molecular understanding of subgroups of CRC with poor prognosis is of vast importance. SOX2 positive tumors have been associated with a poor patient outcome, but the functional role of SOX2 in CRC patient prognosis is still unclear.MethodsAn in vitro cell culture model expressing SOX2 was used to investigate the functional role of SOX2 in CRC. In vitro findings were verified using RNA from fresh frozen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 55 publications
(65 reference statements)
8
58
0
Order By: Relevance
“…Similarly, activation of EGFR also results in overexpression of SNAIL, most likely regulated by the p38 MAPK, ERK1/2 and the AKT/GSK-3b pathways (38). Interestingly, it has been reported that SOX2 and SNAIL play an essential role in the regulation of self-renewal, expansion of CSCs and metastasis in several cancers, including CRC (43,44). Here, we found that ginsenoside Rd inhibited the CSCs maintenance and cell mobility through downregulation of SOX2 and SNAIL as the downstream of EGFR/pAKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, activation of EGFR also results in overexpression of SNAIL, most likely regulated by the p38 MAPK, ERK1/2 and the AKT/GSK-3b pathways (38). Interestingly, it has been reported that SOX2 and SNAIL play an essential role in the regulation of self-renewal, expansion of CSCs and metastasis in several cancers, including CRC (43,44). Here, we found that ginsenoside Rd inhibited the CSCs maintenance and cell mobility through downregulation of SOX2 and SNAIL as the downstream of EGFR/pAKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that CD24 and SOX2 are associated with a more undifferentiated and more cancer stem cell-like phenotype. 7,36,37 Both SOX2 and CD24 have also been linked to an increased therapy resistance. [38][39][40][41] This is in line with our data demonstrating that in melanoma cells an increased expression level of SOX2 or CD24 resulted in a higher tolerance toward BRAFis, while the depletion of SOX2 via KD showed higher sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, transcription factor SRY (sexdetermining region Y)-box 2 (Sox2) is a key regulator of the self-renewing capability of CSCs (Boumahdi et al, 2014). Sox2 is overexpressed in various cancers and is associated with cancer progression and poor prognosis Lundberg et al, 2016). In particular, Sox2 is a pivotal prognostic marker that is correlated with the clinical-pathologic characteristics in lung cancer (Chou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%